Young Registered Nurses' Intention to Leave the Profession and Professional Turnover in Early Career: A Qualitative Case Study - Flinkman, Mervi (Hindawi Publishing Corporation, 2013)
In a time of global nursing shortages an alarming number of young registered nurses have expressed a willingness to leave the profession. In this qualitative case study we investigate in depth why young nurses leave nursing profession and reeducate themselves for a new career. The study is based on longitudinal interviews of three young registered nurses in Finland. These nurses were first interviewed between December 2006 and May 2007, when they were 29–32 years old and having an intention to leave the profession. The second interview took place four years later, from January 2011 to March 2011 when all of them had made the transition to a new career. Data were analyzed in two stages. In the first stage, comprehensive career story narratives were formed on the basis of the interviews. In the second stage, emerging themes in these stories were compared, contrasted, and interpreted in the context of the overall career histories. Nursing as a second career choice and demanding work content as well as poor practice environment and the inability to identify with the stereotypical images of nurses were main themes that emerged from these career stories. The results of this interpretative qualitative study reflect a shift toward insights into understanding professional turnover as a complex and long-lasting process.